A three-protection coating composition for thermal paper and a preparation method thereof
Patent Information
- Application Number
- CN202611254612.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]本发明的目的在于提供一种热敏纸用三防涂层组合物及其制备方法,通过复合共聚乳液、填料和烷基烯酮二聚体的构建实现了高疏水、高疏油阻隔,杜绝高湿与油污环境渗色;此外,还将聚乙烯蜡、巴西棕榈蜡和石蜡进行复配,大幅提升了涂层的耐摩擦性能,有效解决了现有技术中存在的涂层无法兼顾防水、防油和防摩擦性能的问题
(1)本发明以甲基丙烯酸异冰片酯、丙烯酸异丁酯和叔碳酸乙烯酯为共聚单体,经自由基共聚制得三元共聚物;同时引入木质素与纳米二氧化硅作为复合填料,构建分级多孔填充结构,实现不同尺度孔隙的精准填充。其中,木质素填充共聚物基体大孔隙,纳米二氧化硅封堵纳米微孔,由此形成致密阻隔层,物理阻断水、油分子的内部渗透通道,显著提升基体抗渗透性能。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of thermal coating compositions, specifically relating to a three-proof coating composition for thermal paper and its preparation method. Background Technology
[0002] Thermal paper, also known as thermal recording paper, is an important variety of specialty paper. After decades of development, direct thermal printing has evolved into a key imaging technology and has been widely applied in numerous scenarios. This technology falls under the category of non-impact printing. Its core mechanism lies in using heat energy to induce physical or chemical changes in the thermal developer layer on the surface of the paper substrate, thereby forming a clear and readable image. This process is characterized by its simplicity and reliability, making it particularly suitable for small-batch, portable printing needs. Compared to other traditional printing methods, thermal printers exhibit significant technological advantages, including high output speed, low operating noise, almost no daily maintenance, and low energy consumption. Based on these advantages, thermal printing has been widely used in many real-time information recording fields, such as fax communication, sales receipts and transaction vouchers, bank statements, lottery tickets, transportation tickets, price tags, and logistics labels.
[0003] Although thermal printing equipment offers an excellent user experience and is highly adaptable to various applications, its imaging effect relies entirely on the functional coating on the surface of the thermal paper. Existing mainstream thermal coating systems, constrained by formulation components and manufacturing processes, still have significant shortcomings. For example, while ordinary polyurethane coatings are moderately priced, they lack density, are prone to bleeding in high-humidity, oily environments, and can reduce printing sensitivity. Bio-based fluorine-free coatings such as chitosan are environmentally friendly and biodegradable, but they are highly hydrophilic, have poor abrasion resistance, and are prone to powdering due to friction, making them unsuitable for high-frequency applications such as logistics labels. Furthermore, with the global phasing out of various fluorine-containing functional coating materials, the market urgently needs high-performance fluorine-free alternatives. Therefore, developing a three-proof coating composition for thermal paper that combines waterproof, oil-proof, and friction-resistant properties is of great significance. Summary of the Invention
[0004] The purpose of this invention is to provide a three-proof coating composition for thermal paper and its preparation method. By constructing a composite copolymer emulsion, filler and alkyl ketone dimer, high hydrophobicity and high oleophobicity barrier are achieved, preventing color bleeding in high humidity and oily environments. In addition, polyethylene wax, carnauba wax and paraffin wax are compounded to greatly improve the friction resistance of the coating, effectively solving the problem that the coating in the prior art cannot simultaneously achieve waterproof, oil-proof and friction-proof properties.
[0005] The objective of this invention can be achieved through the following technical solutions: A three-proof coating composition for thermal paper, the coating composition comprising the following raw materials in parts by weight: 7-13 parts by weight of composite wax emulsion, 10-14 parts by weight of composite dispersion, 46-50 parts by weight of composite copolymer emulsion, 15-20 parts by weight of alkyl ketene dimer emulsion, and 0.5-1.5 parts by weight of defoamer.
[0006] As a preferred embodiment of the present invention, the preparation method of the composite wax emulsion is as follows: Polyethylene wax, carnauba wax, and paraffin wax are stirred at a controlled temperature until melted to obtain a blend. Fatty alcohol polyoxyethylene ether is dissolved in deionized water and then added dropwise to the blend at a uniform rate. The mixture is stirred to emulsify, homogenized, and cooled to obtain a composite wax emulsion, which is then sealed for later use.
[0007] As a preferred embodiment of the present invention, the polyethylene wax comprises 6-10 parts by weight, carnauba wax comprises 5-7 parts by weight, paraffin wax comprises 1-2 parts by weight, fatty alcohol polyoxyethylene ether comprises 1-3 parts by weight, and deionized water comprises 20-26 parts by weight.
[0008] Furthermore, the fatty alcohol polyoxyethylene ether includes AEO-7 or AEO-3.
[0009] Preferably, the fatty alcohol polyoxyethylene ether comprises AEO-7.
[0010] As a preferred embodiment of the present invention, the temperature of the temperature-controlled stirring is 95-100℃, the stirring and emulsification speed is 1200-1400r / min and the time is 40-60min, the homogenization pressure is 22-26MPa and the number of times is 2, and the cooling is cooling to room temperature.
[0011] As a preferred embodiment of the present invention, the preparation method of the composite dispersion is as follows: Alkaline lignin and deionized water are mixed and stirred under controlled temperature once. Sodium polyacrylate and nano silica are added and stirred under controlled temperature a second time. After homogenization, cooling and standing are performed to obtain the composite dispersion.
[0012] As a preferred embodiment of the present invention, the alkaline lignin is 4-8 parts by weight, the deionized water is 34-38 parts by weight, the sodium polyacrylate is 0.3-0.6 parts by weight, and the nano silica is 3-5 parts by weight.
[0013] Furthermore, the average particle size of the nano-silica is 70-90 nm.
[0014] As a preferred embodiment of the present invention, the temperature of the first temperature-controlled stirring is 55-65℃ and the time is 30-45 min; the speed of the second temperature-controlled stirring is 3500-4000 r / min, the temperature is 60-70℃ and the time is 1-2 h; the pressure of the homogenization is 13-15 MPa and the number of times is 1; the cooling is cooling to room temperature; and the standing time is 1-2 h.
[0015] As a preferred embodiment of the present invention, the preparation method of the composite copolymer emulsion is as follows: Fatty alcohol polyoxyethylene ether and deionized water are mixed and stirred to obtain mixture A; isobornyl methacrylate, isobutyl acrylate and ethylene tert-carbonate are mixed evenly to obtain mixture B; nitrogen gas is introduced, and mixture B and a 1% ammonium persulfate aqueous solution are added to mixture A, the temperature is controlled and stirred, the pH is adjusted, cooled and sieved to obtain the composite copolymer emulsion.
[0016] As a preferred embodiment of the present invention, the fatty alcohol polyoxyethylene ether is 0.6-1.2 parts by weight, the deionized water is 62-68 parts by weight, the isobornyl methacrylate is 12-18 parts by weight, the isobutyl acrylate is 8-14 parts by weight, the ethylene tert-carbonate is 5-9 parts by weight, and the ammonium persulfate aqueous solution is 0.2-0.4 parts by weight.
[0017] Furthermore, the fatty alcohol polyoxyethylene ether includes AEO-7.
[0018] As a preferred embodiment of the present invention, the mixing and stirring time is 20-30 minutes, the temperature of the temperature-controlled stirring is 70-80℃ and the time is 2.5-3.5 hours, the pH adjustment is to add ammonia water to adjust the pH to 6.9-7.5, the cooling is to cool to room temperature, and the sieving is to pass through a 200-220 mesh sieve.
[0019] As a preferred embodiment of the present invention, the defoamer is an aqueous silicone emulsion.
[0020] A method for preparing a three-proof coating composition for thermal paper specifically includes the following steps: A composite dispersion, an alkyl ketene dimer emulsion, and a composite wax emulsion are added sequentially to a composite copolymer emulsion. After stirring evenly, an antifoaming agent is added, the pH is adjusted, and the mixture is filtered and allowed to stand for aging to obtain a three-proof coating composition for thermal paper.
[0021] As a preferred embodiment of the present invention, the pH adjustment is achieved by adding ammonia to adjust the pH to 6.9-7.5, the filtration is performed by passing the solution through a 180-200 mesh filter, and the settling and maturation time is 12-16 hours.
[0022] The beneficial effects of this invention are: (1) This invention uses isobornyl methacrylate, isobutyl acrylate, and ethylene tert-carbonate as comonomers to prepare a terpolymer via free radical copolymerization; at the same time, lignin and nano-silica are introduced as composite fillers to construct a hierarchical porous filling structure, achieving precise filling of pores of different sizes. Among them, lignin fills the large pores of the copolymer matrix, and nano-silica seals the nano-micropores, thereby forming a dense barrier layer that physically blocks the internal permeation channels of water and oil molecules, significantly improving the matrix's anti-permeation performance.
[0023] (2) In this invention, isobornyl groups from isobornyl methacrylate, tertiary carbon groups from ethylene tertiary carbonate, and isobutyl groups from isobutyl acrylate are introduced into the terpolymer skeleton of the system through free radical copolymerization. During film formation, the introduced low surface energy groups can form a hydrophobic interface on the coating surface, reducing the wetting and penetration of external liquids into the coating. At the same time, the nonpolar alkyl groups and alicyclic structures on the copolymer molecules are superimposed and arranged, which can also hinder the wetting and adhesion of oil molecules to a certain extent, thereby improving the oil-repellent performance of the coating. On this basis, this invention also forms covalent bonds by the interaction of alkyl ketene dimers with lignin and hydroxyl groups in the terpolymer, so that the alkyl ketene dimers are firmly anchored on the coating surface. The long alkyl hydrophobic carbon chains are oriented outward, which can construct a dense nonpolar hydrophobic and oleophobic surface layer, further assisting the terpolymer in improving the overall waterproof and oil-repellent performance of the coating.
[0024] (3) The present invention uses polyethylene wax, carnauba wax and paraffin wax. Due to their low surface energy characteristics, the three are enriched on the surface through the floating effect when the coating is formed, forming a continuous, uniform, dense and hard wax film. This wax film can improve the surface smoothness of the coating, reduce the interfacial friction coefficient, reduce friction and wear, and significantly improve the anti-friction performance of the coating. Detailed Implementation
[0025] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0026] The alkaline lignin used in this invention was purchased from Wuhan Jiyesheng Chemical Co., Ltd. The sodium polyacrylate used was purchased from Jinan Daorong Chemical Co., Ltd. The fatty alcohol polyoxyethylene ether AEO-7 used was purchased from: Haian Petrochemical Plant, Jiangsu Province; The alkyl ketene dimer emulsion used, brand name: LS-A20, was purchased from Wuxi Tianxin Chemical Co., Ltd. The aqueous silicone emulsion used, brand name: AT-470, was purchased from Foshan Nanhai Datian Chemical Co., Ltd. The above will not be repeated hereafter.
[0027] Example 1 This embodiment prepares a three-proof coating composition for thermal paper using the following method: (1) Stir 6g of polyethylene wax, 5g of carnauba wax and 1g of paraffin wax at 100℃ until melted to obtain a blend. Dissolve 2g of fatty alcohol polyoxyethylene ether AEO-7 in 20g of deionized water and add it to the blend at a uniform rate. Stir and emulsify at 1400r / min for 60min. Homogenize twice at 22MPa and cool to room temperature to obtain a composite wax emulsion. Seal and store for later use. (2) Mix 8g of alkaline lignin and 34g of deionized water and stir at 55℃ for 45min. Add 0.3g of sodium polyacrylate and 4g of nano silica with an average particle size of 70nm and stir at 65℃ for 1h at a speed of 4000r / min. Homogenize once under 14MPa pressure, cool to room temperature and stand for 1h to obtain the composite dispersion for later use. (3) Mix 0.9g of fatty alcohol polyoxyethylene ether AEO-7 and 68g of deionized water for 25min to obtain mixture A, and set aside; take 18g of isoborneol methacrylate, 11g of isobutyl acrylate and 7g of tert-butyl carbonate and mix evenly to obtain mixture B, and set aside; purge with nitrogen, add the prepared mixture B and 0.2g of ammonium persulfate aqueous solution with a mass concentration of 1% to the prepared mixture A, stir at 70℃ for 3.5h, add ammonia water to adjust pH=7.2, cool to room temperature, and pass through a 200-mesh sieve to obtain the composite copolymer emulsion, and set aside; (4) Take 48g of the prepared composite copolymer emulsion, add 14g of the prepared composite dispersion, 20g of alkyl ketene dimer emulsion and 7g of composite wax emulsion in sequence, stir evenly, add 0.5g of defoamer, add ammonia water to adjust pH=7.5, pass through a 190 mesh filter, let stand and mature for 16h to obtain the three-proof coating composition for thermal paper.
[0028] Example 2 This embodiment prepares a three-proof coating composition for thermal paper using the following method: (1) Stir 8g of polyethylene wax, 7g of carnauba wax and 1.5g of paraffin wax at a controlled temperature of 97.5℃ until melted to obtain a blend. Dissolve 1g of fatty alcohol polyoxyethylene ether AEO-7 in 23g of deionized water and add it dropwise into the blend at a uniform rate. Stir and emulsify at a speed of 1600r / min for 40min. Homogenize twice at a controlled pressure of 26MPa. Cool to room temperature to obtain a composite wax emulsion. Seal and store for later use. (2) Mix 6g of alkaline lignin and 38g of deionized water and stir at 60℃ for 37.5min. Add 0.6g of sodium polyacrylate and 3g of nano silica with an average particle size of 90nm and stir at 70℃ for 1.5h at a speed of 3500r / min. Homogenize once under 15MPa pressure, cool to room temperature and let stand for 1h to obtain the composite dispersion for later use. (3) Mix 1.2g of fatty alcohol polyoxyethylene ether AEO-7 and 62g of deionized water for 20min to obtain mixture A, and set aside; take 15g of isoborneol methacrylate, 8g of isobutyl acrylate and 9g of tert-butyl carbonate and mix evenly to obtain mixture B, and set aside; purge with nitrogen, add the prepared mixture B and 0.4g of ammonium persulfate aqueous solution with a mass concentration of 1% to the prepared mixture A, stir at 75℃ for 3h, add ammonia water to adjust pH=6.9, cool to room temperature, and pass through a 220 mesh sieve to obtain the composite copolymer emulsion, and set aside; (4) Take 46g of the prepared composite copolymer emulsion, add 10g of the prepared composite dispersion, 15g of alkyl ketene dimer emulsion and 13g of composite wax emulsion in sequence, stir evenly, add 1.5g of defoamer, add ammonia water to adjust pH=7.2, pass through a 180 mesh filter, let stand and mature for 12h to obtain the three-proof coating composition for thermal paper.
[0029] Example 3 This embodiment prepares a three-proof coating composition for thermal paper using the following method: (1) Stir 10g of polyethylene wax, 7g of carnauba wax and 2g of paraffin wax at 95℃ until melted to obtain a blend. Dissolve 3g of fatty alcohol polyoxyethylene ether AEO-7 in 26g of deionized water and add it dropwise into the blend at a uniform rate. Stir and emulsify at 1200r / min for 50min. Homogenize twice at 24MPa and cool to room temperature to obtain a composite wax emulsion. Seal and store for later use. (2) Mix 4g of alkaline lignin and 36g of deionized water and stir at 65°C for 30min. Add 0.45g of sodium polyacrylate and 5g of nano silica with an average particle size of 80nm and stir at 60°C for 2h at a speed of 3750r / min. Homogenize once under 13MPa pressure, cool to room temperature and stand for 2h to obtain the composite dispersion for later use. (3) Mix 0.6g of fatty alcohol polyoxyethylene ether AEO-7 and 65g of deionized water for 30min to obtain mixture A, and set aside; take 12g of isoborneol methacrylate, 14g of isobutyl acrylate and 5g of tert-carbonate and mix evenly to obtain mixture B, and set aside; purge with nitrogen, add the prepared mixture B and 0.3g of ammonium persulfate aqueous solution with a mass concentration of 1% to the prepared mixture A, stir at 80℃ for 2.5h, add ammonia water to adjust pH=7.5, cool to room temperature, and pass through a 210 mesh sieve to obtain the composite copolymer emulsion, and set aside; (4) Take 50g of the prepared composite copolymer emulsion, add 12g of the prepared composite dispersion, 17.5g of alkyl ketene dimer emulsion and 10g of composite wax emulsion in sequence, stir evenly, add 1g of defoamer, add ammonia water to adjust pH=6.9, pass through a 200-mesh filter, let stand and mature for 14h to obtain the three-proof coating composition for thermal paper.
[0030] Comparative Example 1 Compared with Example 2, the difference is that polyethylene wax is not added in step (1) of Comparative Example 1, and the amount of carnauba wax is 11g and the amount of paraffin wax is 5.5g. The other preparation steps and parameters remain unchanged.
[0031] Comparative Example 2 Compared with Example 2, the difference is that carnauba wax was not added in step (1) of Comparative Example 2, and the amount of polyethylene wax was 12g and the amount of paraffin wax was 4.5g. The other preparation steps and parameters remained unchanged.
[0032] Comparative Example 3 Compared with Example 2, the difference is that no paraffin was added in step (1) of Comparative Example 3, and the amount of polyethylene wax was 9g and the amount of carnauba wax was 7.5g. The other preparation steps and parameters remained unchanged.
[0033] Comparative Example 4 Compared with Example 2, the difference is that no alkaline lignin was added in step (2) of Comparative Example 4, and the amount of nano-silica was 9g, while the other preparation steps and parameters remained unchanged.
[0034] Comparative Example 5 Compared with Example 2, the difference is that no nano-silica was added in step (2) of Comparative Example 5, and the amount of alkaline lignin was 9g, while the other preparation steps and parameters remained unchanged.
[0035] Comparative Example 6 Compared with Example 2, the difference is that isobornyl methacrylate is not added in step (3) of Comparative Example 6, while the other preparation steps and parameters remain unchanged.
[0036] Comparative Example 7 Compared with Example 2, the difference is that isobutyl acrylate is not added in step (3) of Comparative Example 7, while the other preparation steps and parameters remain unchanged.
[0037] Comparative Example 8 Compared with Example 2, the difference is that ethylene tert-carbonate is not added in step (3) of Comparative Example 8, while the other preparation steps and parameters remain unchanged.
[0038] Comparative Example 9 Compared with Example 2, the difference is that alkyl ketene dimer emulsion was not added in step (4) of Comparative Example 9, while the other preparation steps and parameters remained unchanged.
[0039] Performance testing The three-proof coating compositions for thermal paper prepared in Examples 1-3 and Comparative Examples 1-9 are applied to the surface of thermal paper by one of the following methods: air knife coating, doctor blade coating, roller coating, doctor bar coating, and curtain coating. After drying, a three-proof coating is formed on the surface of the thermal paper.
[0040] (1) Waterproof and oil-proof performance test: A drop of 5 μL of deionized water and castor oil were dropped onto the coating surface of the thermal paper prepared by the three-proof coating composition of Examples 1-3 and Comparative Examples 4-9, respectively. The contact angle of the coating was measured by a contact angle measuring instrument. The larger the contact angle, the better the waterproof and oil-proof performance. The results are shown in Table 1.
[0041] Table 1
[0042] As can be seen from Table 1, the coatings of the three-proof coating compositions for thermal paper prepared in Examples 1-3 of the present invention have higher water contact angles and oil contact angles than those in Comparative Examples 4-9. This indicates that the present invention uses isoborneol methacrylate, isobutyl acrylate, and ethylene tert-carbonate as comonomers, and simultaneously introduces lignin, nano-silica, and alkyl ketene dimers, which can improve the overall waterproof and oil-proof performance of the coating.
[0043] (2) Anti-friction performance test: The anti-friction performance of the coatings prepared by the three-proof coating compositions of thermal paper of Examples 1-3 and Comparative Examples 1-3 was tested according to GB / T 28210-2024. The results are expressed as image retention rate, and the results are shown in Table 2.
[0044] Table 2
[0045] As can be seen from Table 2, the image retention rates of the thermal paper three-proof coating compositions prepared in Examples 1-3 of the present invention are all higher than those of Comparative Examples 1-3. This indicates that the use of polyethylene wax, carnauba wax and paraffin wax in the present invention can synergistically improve the surface smoothness of the coating, reduce the interfacial friction coefficient, reduce friction and wear, and significantly improve the anti-friction performance of the coating.
[0046] In the description of this specification, the references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0047] The above description is merely an example and illustration of the concept of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the concept of the invention or exceed the scope defined in the claims, they should all fall within the protection scope of the present invention.
Claims
1. A three-proof coating composition for thermal paper, characterized in that, The coating composition comprises the following raw materials in parts by weight: 7-13 parts by weight of composite wax emulsion, 10-14 parts by weight of composite dispersion, 46-50 parts by weight of composite copolymer emulsion, 15-20 parts by weight of alkyl ketene dimer emulsion, and 0.5-1.5 parts by weight of defoamer.
2. The three-proof coating composition for thermal paper according to claim 1, characterized in that, The specific preparation method of the composite wax emulsion is as follows: Polyethylene wax, carnauba wax, and paraffin wax are stirred at a controlled temperature until melted to obtain a blend. Fatty alcohol polyoxyethylene ether is dissolved in deionized water and then added dropwise to the blend at a uniform rate. The mixture is stirred to emulsify, homogenized, and cooled to obtain a composite wax emulsion, which is then sealed for later use.
3. The method for preparing the composite wax emulsion according to claim 2, characterized in that, The polyethylene wax comprises 6-10 parts by weight, carnauba wax comprises 5-7 parts by weight, paraffin wax comprises 1-2 parts by weight, fatty alcohol polyoxyethylene ether comprises 1-3 parts by weight, and deionized water comprises 20-26 parts by weight.
4. The method for preparing the composite wax emulsion according to claim 2, characterized in that, The temperature of the temperature-controlled stirring is 95-100℃, the stirring speed of the emulsification is 1200-1400 r / min and the time is 40-60 min, the homogenization pressure is 22-26 MPa and the number of times is 2, and the cooling is cooling to room temperature.
5. The three-proof coating composition for thermal paper according to claim 1, characterized in that, The specific method for preparing the composite dispersion is as follows: Alkaline lignin and deionized water are mixed and stirred under controlled temperature once. Sodium polyacrylate and nano silica are added and stirred under controlled temperature a second time. After homogenization, cooling and standing are performed to obtain the composite dispersion.
6. The method for preparing the composite dispersion according to claim 5, characterized in that, The alkaline lignin is 4-8 parts by weight, the deionized water is 34-38 parts by weight, the sodium polyacrylate is 0.3-0.6 parts by weight, and the nano silica is 3-5 parts by weight.
7. The method for preparing the composite dispersion according to claim 5, characterized in that, The temperature of the first temperature-controlled stirring is 55-65℃ and the time is 30-45 min. The speed of the second temperature-controlled stirring is 3500-4000 r / min, the temperature is 60-70℃, and the time is 1-2 h. The pressure of the homogenization is 13-15 MPa and the number of times is 1. The cooling is to cool to room temperature. The standing time is 1-2 h.
8. The three-proof coating composition for thermal paper according to claim 1, characterized in that, The specific method for preparing the composite copolymer emulsion is as follows: Fatty alcohol polyoxyethylene ether and deionized water are mixed and stirred to obtain mixture A; isobornyl methacrylate, isobutyl acrylate and ethylene tert-carbonate are mixed evenly to obtain mixture B; nitrogen gas is introduced, and mixture B and a 1% ammonium persulfate aqueous solution are added to mixture A, the temperature is controlled and stirred, the pH is adjusted, cooled and sieved to obtain the composite copolymer emulsion.
9. The method for preparing the composite copolymer emulsion according to claim 8, characterized in that, The fatty alcohol polyoxyethylene ether is 0.6-1.2 parts by weight, deionized water is 62-68 parts by weight, isobornyl methacrylate is 12-18 parts by weight, isobutyl acrylate is 8-14 parts by weight, ethylene tert-carbonate is 5-9 parts by weight, and ammonium persulfate aqueous solution is 0.2-0.4 parts by weight.
10. A method for preparing a three-proof coating composition for thermal paper as described in any one of claims 1-9, characterized in that, Specifically, the steps include the following: A composite dispersion, an alkyl ketene dimer emulsion, and a composite wax emulsion are added sequentially to a composite copolymer emulsion. After stirring evenly, an antifoaming agent is added, the pH is adjusted, and the mixture is filtered and allowed to stand for aging to obtain a three-proof coating composition for thermal paper.